The IMF and Human Development : A Dialogue with Civil Society - Camdessus, Michel (Pamphlet Series; Pamphlet Series, No., 2000)
During his tenure as Managing Director of the IMF, and in his interactions with civil society, Michel Camdessus was asked many questions related to the IMF's role in development. This pamphlet collects questions frequently asked by civil society around the world and the responses given by Mr. Camdessus that help to clarify the IMF position on human development.